Low-temperature heat capacities for EMoO4 (E=Mg, Sr, Ba) substances formed in nuclear fuel waste glasses. (January 2022) - Koç, Hüseyin; Köse, Okan; Eser, Erhan
Abstract: Thermodynamic properties of various crystalline solids are evaluated from low-temperature heat capacity measurements, in the temperature range 0–300 K using semi-empirical models. Previous studies include fit functions with many coefficients resulting in almost perfect agreement with experimental data. The heat capacities of the end-members of the yellow phase formed in the nuclear fuel waste glasses can be fitted by simple Debye-Einstein integral formula to avoid overfitting. In this study, the heat capacities, the characteristic temperatures ( θ D, θ E 1, θ E 2 ) and the fitting parameters ( m, n 1 and n 2 ) of MgMoO4, SrMoO4 and BaMoO4 were determined by fitting the Debye-Einstein integral to the experimental heat capacity. The Debye temperatures θ D of MgMoO4, SrMoO4 and BaMoO4 are 546.15 K, 496.3 K and 420.6 K, respectively, and their Einstein temperatures ( θ E 1, θ E 2 ) are (162.46, 1185.25) K, (169.41, 1040.56) K and (125.3, 958.87) K. It is shown from the results that the Debye-Einstein function used in the present study was found to be in good agreement with the experimental data.